Gut leakage markers in response to strenuous exercise in patients with suspected coronary artery disease. (14th October 2021) - Aune, S K; Cwikiel, J; Flaa, A; Arnesen, H; Solheim, S; Awoyemi, A; Troeseid, M; Seljeflot, I; Helseth, R
Abstract: Introduction: Although regular physical activity is associated with reduced risk of cardiovascular disease (CVD), acute vigorous exercise seems to transiently increase the risk of acute coronary events in patients with underlying CVD. Some studies have reported regular physical activity to associate with microbial diversity, whereas elevated levels of gut leakage markers have been shown after strenuous exercise in healthy individuals. Any predictive value of a temporary increase in gut leakage markers on the risk of coronary events in susceptible individuals is unknown. Purpose: We aimed to explore gut leakage markers in response to a bout of strenuous exercise in patients with symptoms of chronic coronary syndrome (CCS). We hypothesized that gut leakage markers would increase after acute strenuous exercise, and that the increase would be higher in patients with angiographically verified CAD. Methods: Patients referred to exercise stress testing or coronary angiography due to symptoms suggestive of CCS were included (n=327). A maximal exercise ECG stress test was performed using a bicycle ergometer. Venous blood samples were drawn at rest prior to the test and within 5 min after the test ended, for analysis of soluble cluster of differentiation 14 (sCD14), lipopolysaccharide-binding protein (LBP) and intestinal fatty-acid binding protein (I-FABP) by ELISAs. Quantification of lipopolysaccharide (LPS) and relative quantification of gene expression of the toll-like receptor 4 (TLR4) in circulating leukocytes was performed in a subset of patients (n=101). Patients then underwent coronary angiography, and were grouped according to the degree of CAD. Results: Of the 287 patients who completed the exercise stress test and coronary angiography, 69 (24%) had no CAD, 88 (31%) had non-significant CAD and 130 (45%) had significant CAD. Mean exercise duration was 10:05±4:46 min and the duration did not differ between the groups. There were no significant differences in resting levels of gut leakage markers between the groups. In the total population, sCD14, LBP and LPS increased significantly after exercise (p<0.0001, all), whereas I-FABP did not. The gene expression of TLR4 decreased significantly after exercise (p<0.0001). There were no differences in exercise-induced changes in any of the measured markers between groups with no CAD, non-significant CAD and significant CAD. Conclusion: In patients with symptoms suggestive of CCS, LPS, LBP and sCD14 increased significantly after strenuous exercise, suggesting that even short bouts of vigorous exercise are associated with gut leakage. The decrease in gene expression of TLR4 may be discussed to be compensatory to the increase in LPS or possibly reflecting an increase in TLR4 translation in response to LPS. The presence of CAD or not did not seem to impact exercise-induced increase in gut leakage markers. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Stein Erik Hagen Foundation for Clinical Heart Research, Olso, Norway